Regulating N Application for Rice Yield and Sustainable Eco-Agro Development in the Upper Reaches of Yellow River Basin, China. (17th June 2014) - Zhang, Aiping; Liu, Ruliang; Gao, Ji; Yang, Shiqi; Chen, Zhe
Abstract : High N fertilizer and flooding irrigation applied to rice on anthropogenic-alluvial soil often result in N leaching and low recovery of applied fertilizer N from the rice fields in Ningxia irrigation region in the upper reaches of the Yellow River, which threatens ecological environment, food security, and sustainable agricultural development. This paper reported the regulating N application for rice yield and sustainable Eco-Agro development in the upper reaches of Yellow River basin. The results showed that reducing and postponing N application could maintain crop yields while substantially reducing N leaching losses to the environment and improving the nitrogen use efficiency. Considering the high food production, the minimum environmental threat, and the low labor input, we suggested that regulating N application is an important measure to help sustainable agricultural development in this region.